The endoplasmic reticulum: the unfolded protein response - Kaufman, Randal (Henry Stewart Talks, 2007)
The secretory pathway, Factor VIII expression induces ER stress, Protein folding: the ultimate and most error prone step in gene expression, The "unfolded protein response" (UPR) ensures fidelity of protein folding, UPR signaling response, Activation of the UPR, Stress signaling from the ER, Role of eIF2 in translation initiation, Translation initiation response to external stimuli, eIF2a phosphorylation is required for UPR, Wolcott-Rallison syndrome, Plasma cell differentiation requires ER expansion, Roles of IRE1a/XBP1 in lymphocyte development, ER-stress-induced transcription through regulated intramembrane proteolysis (RIP), CREBH and ATF6, ER-stress-induced apoptosis, ER stress and oxidative stress, UPR-induced alterations in gene expression